Effect of Bioagents in Different Formulations towards Rhizome Rot Management of Turmeric in Eastern Ghat High Land Zone of Odisha - Behera, Sunita; Sial, Parsuram; Biswal, Gayatri; Mohapatra, Pavitra Mohan; Panda, Prasant Kumar; Mishra, Ipsita Odisi Priyadarsini; Prusti, Arjun Mohan (International Journal of Economic Plants, 2024)
A field experiment was conducted at High Altitude Research Station, Pottangi under Odisha University of Agriculture and Technology during the month of May to January 2018–19, 2019–2020 and 2020–21 to find out effect of bioagents in different formulations towards rhizome rot management in turmeric. Seven treatments were tested in the experiments T1: Tricho capsule (Trichoderma harzianum @ 1×106 cfu g-1) @ 1 capsule/120 l. of water. T2: GRB-35 capsule (Bacillus amyloliquefaciens @ 1×108 cfu g-1) @ 1 capsule/120 l. of water, T3: Tricho talc (T. harzianum @ 1×106 cfu g-1) powder @ 8.5 g l-1 of water, T4: GRB-35 talc powder (Bacillus amyloliquefaciens @ 1×108 cfu g-1) 8.5 g l-1 of water , T5: Tricho power liquid (Trichoderma viride @ 1×106 cfu ml-1) @ 5 ml l-1 of water, T6: Monas (Pseudomonas fluorescens @ 108 cfu ml-1) liquid @ 10 ml l-1 of water and T7: Control without any treatments. In each treatment rhizome treatment for 30 mins and basal applications of bioagents done at 45 and 90 DAS @ 5 l bed-1. Data on percent disease intensity, yield and B:C ratio were recorded at 45, 60 and 90 DAS. The lowest percent disease intensity (8.94%), highest fresh rhizome yield (21.06 t ha-1) and B:C ratio (1.72:1) was found in the treatment T5 followed by T1 with (10.33%) disease intensity, (20.57 t ha-1) yield and (1.69:1) B:C ratio.